Fatty Acid and Carnitine Metabolism Are Dysregulated in Systemic Sclerosis Patients - Ottria, A.; Hoekstra, A. T.; Zimmermann, M.; van der Kroef, M.; Vazirpanah, N.; Cossu, M.; Chouri, E.; Rossato, M.; Beretta, L.; Tieland, R. G.; Wichers, C. G. K.; Stigter, E.; et al. (Frontiers in Immunology, 2020)
22 Abstract 23 Systemic sclerosis (SSc) is a rare chronic disease of unknown pathogenesis characterized by fibrosis 24 of the skin and internal organs, vascular alteration and dysregulation of the immune system. In order 25 to better understand the immune system and its perturbations leading to diseases, the study of the 26 mechanisms regulating cellular metabolism has gained a wide interest. Here we assessed the 27 metabolical status of plasma and dendritic cells (DCs) in patients with SSc. We identified a 28 dysregulated metabolomic signature in carnitine in both, circulation (plasma) and intracellularly in 29 DCs of SSc patients. In addition, we confirmed carnitine alteration in the circulation of SSc patients 30 in three independent plasma measurements from two different cohorts and identified dysregulation of 31 fatty acids. We hypothesized that fatty acid and carnitine alterations contribute to potentiation of 32 inflammation in SSc. Incubation of healthy and SSc dendritic cells with etoposide, a carnitine 33 transporter inhibitor, inhibited the production of pro-inflammatory cytokines such as IL-6 through 34 inhibition of fatty acid oxidation. These findings shed light on the altered metabolic status of the 35 immune system in SSc patients and opens potential novel avenues to reduce inflammation.